THE FLOUTING OF MAXIMS IN SARAH SECHAN TALK SHOW EPISODE “FITRI TROPICA” ON NET TV - NASUTION, DEWI ANDRIANA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Cooperative Principle, Flouting of Maxims, Sarah Sechan Talk ShowThis study examines the flouting of maxims that happens in Sarah Sechan talk show in the episode of Fitri Tropica on Net TV. This study is conducted to answer the problems of the study namely what maxims that are flouted and to what extent the maxims are flouted by the host and the guest in Sarah Sechan talk show episode of Fitri Tropica on Net TV in terms of the classification of the flouted maxims, the implication of flouted of maxims and the purpose of the flouting of maxims.This study uses qualitative approach since the data is performed in the form ofword rather than numbers. The data is the utterances that contain flouted maxims and the data source is the transcription of the talk show which is the episode with the guest Fitri Tropica. The researcher collects the data by reading the transcription very carefully and then listing the utterances that contain flouted maxims. Thus, the researcher identifies the flouted maxims and analyzes them and finally draws a conclusion.The researcher found that all maxims are flouted in the show. There are 46utterances that contain flouting of maxims in the show. The most frequently flouted maxim is maxim of relation which is 15 utterances. The second most frequently flouted maxim is maxim of quality which is 12 utterances and third is maxim of quantity which is 8 utterances. The least frequently flouted maxim is maxim of manner which is 4 utterances. The researcher also found there are 7 utterances which contain overlap maxims. The flouting frequently happens because the speaker wants to avoid being explicit in answering the question related to personal life. Besides, the flouting is frequently used to create a joke in the sake of entertainment in the show.For the next researcher, it is recommended that they conduct the study offlouting of maxims using the other theory. The researcher also suggests the next researchers conduct a research on the flouting of maxims in other object for example; radio shows, comics, books, magazines or videos on the internet to broaden the understanding of flouting of maxims phenomenon.